2011
DOI: 10.17159/2413-3051/2011/v22i3a3219
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy, poverty alleviation and developing nations: Evidence from Senegal

Abstract: The desire to increase energy access remains a strong driving force for poverty alleviation in rural areas of developing countries. The supply of modern energy facilitates the improvement of human living conditions and the productivity of sectors. It also contributes by reducing the time spent, mainly for women and children, in collecting biomass and therefore can provide an opportunity for an increase in the education level of children and for women empowerment. This paper shows how renewable energy facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 42 publications
1
18
0
3
Order By: Relevance
“…Existing empirical literature on the impact of energy consumption on poverty reduction are quite scant. Few that available were done by Okwanya and Abah (2018), Pachauri and Spreng (2004), Thiam (2011), Ogbeide-Osaretin (2020), Nkomo (2007), Okwanya et al (2015), Hussein and Filho (2012) and Kousar et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Existing empirical literature on the impact of energy consumption on poverty reduction are quite scant. Few that available were done by Okwanya and Abah (2018), Pachauri and Spreng (2004), Thiam (2011), Ogbeide-Osaretin (2020), Nkomo (2007), Okwanya et al (2015), Hussein and Filho (2012) and Kousar et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Food access occurs when a household is empowered to provide a balanced diet for all its members [81,82]. In Kenya, food availability is determined by cereal supply particularly maize.…”
Section: Energy Poverty and Calorific Intakementioning
confidence: 99%
“…Hence access to modern energy sources improves literacy levels. A study conducted in Nicaragua showed a positive and significant relationship between a home having electricity and all the children completing primary school [120] and in Philippines, a similar study showed a correlation between energy access and education [81]. Education empowers individuals to get well-paying jobs, thus enhancing their consumption power which can translate to higher living standards.…”
Section: Energy Poverty and Literacy Levelsmentioning
confidence: 99%
“…Agricultural and agribusiness by-products are abundant with very good potential for on-grid and off-grid electricity generation, while plant species such as plant oil, jatropha-curcas, cattails, sunflower, cotton, castor, sweet sorghum etc. are expected to play a significant role in biofuel production in Senegal [133,136,[139][140][141].…”
Section: Re In Senegalmentioning
confidence: 99%